A complex of p190RhoGAP-A and anillin modulates RhoA-GTP and the cytokinetic furrow in human cells - Manukyan, Arkadi (J Cell Sci, 2015)
The cytokinetic furrow is organized by the RhoA GTPase, which recruits actin and myosin II to the furrow and drives contractility. Here, we show that the RhoA GTPase-activting protein (GAP) p190RhoGAP-A (also known as ARHGAP35) has a role in cytokinesis and is involved in regulating levels of RhoA-GTP and contractility. Cells depleted of p190RhoGAP-A accumulate high levels of RhoA-GTP and markers of high RhoA activity in the furrow, resulting in failure of the cytokinetic furrow to progress to abscission. The loss of p190RhoGAP-A can be rescued by a low dose of the myosin II inhibitor blebbistatin, suggesting that cells fail cytokinesis because they have too much myosin activity. p190RhoGAP-A binds the cytokinetic organizer anillin, and mutants of p190RhoGAP-A that are unable to bind anillin or unable to inactivate RhoA fail to rescue cytokinesis defects in p190RhoGAP-A-depleted cells. Taken together, these data demonstrate that a complex of p190RhoGAP-A and anillin modulates RhoA-GTP levels in the cytokinetic furrow to ensure progression of cytokinesis.